Strategi Penyusunan Kontrak Yang Mengurangi Resiko Sengketa Bisnis - Frensiska Ardhiyaningrum (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
This article examines effective contract drafting approaches for reducing the likelihood of disputes in business dealings. Contracts are a crucial legal tool in an increasingly complicated corporate world, governing the rights and obligations of the parties. However, many contracts are poorly constructed, causing uncertainty and the possibility of lawsuits. The paper discusses several contract drafting approaches, such as employing clear and straightforward wording, establishing realistic terms and conditions, and incorporating a dispute resolution mechanism. Furthermore, this study emphasizes the need of completing due diligence on all parties involved and understanding the necessary legal background. By taking these procedures, parties can lessen the chance of disputes while boosting legal certainty throughout contract implementation. The study's findings are expected to assist legal experts and business owners in developing more effective and efficient contract language.